Urban wastewater overflows as hotspots for dissemination of bacteria producing extended-spectrum β-lactamases and carbapenemases in the Suquía River, Argentina - Ruiz, Susana Eugenia; Morandini, Fabrizzio Nicolas; Panzetta, María Emilia; Lipari, Flavio Gabriel; Irrazábal, María Gabriela; Toselli, Ricardo; Der Ohannesian, Martín; Amieva, Cristian; Valdes, María Eugenia; Giraudo, Federico Javier; Rollán, María del Rosario; Amé, Valeria; et al. (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) is a critical global challenge, yet the role of environmental dissemination of antibiotic-resistant bacteria remains underexplored, particularly in developing regions. This study investigated urban wastewater overflows from public streets as vectors for extended-spectrum-β-lactamase (ESBL)- and carbapenemase-producing Enterobacterales and Aeromonas in the Suquía River (Córdoba, Argentina). Sixty-two water samples were analyzed for coliform counts, antimicrobial susceptibility, and resistance genes. Horizontal gene transfer was assessed by conjugation. Sixty-five ESBL- and/or carbapenemase-producing isolates were recovered, including six carbapenemase producers subjected to whole-genome sequencing (WGS). Urban wastewater exhibited coliform levels >108 MPN/100 mL, while river counts increased 2–5 logs at urban and downstream sites compared to upstream, where no resistant strains were detected. ESBL- and/or carbapenemase-producers occurred in ~70% of wastewater and river samples, mainly Escherichia coli harboring blaCTX-M. Carbapenemase producers carried blaKPC-2 or blaNDM-1 in Enterobacter, Klebsiella, Citrobacter, and Aeromonas caviae. WGS revealed extensive resistomes, virulence genes, and plasmid replicons, including IncU and IncA/C2 linked to carbapenemases. Conjugation confirmed plasmid-mediated transfer of β-lactamase genes, and genetic context analysis identified clinically recognized transposons. Notably, Enterobacter kobei and Aeromonas caviae from the river carried blaKPC-2 on plasmidic contigs combining clinical and environmental elements, consistent with genetic exchange within aquatic ecosystems and transfer of clinically significant resistance determinants to species adapted for riverine survival. These findings identify urban wastewater overflows as AMR hotspots that facilitate the dissemination of multidrug-resistant bacteria and mobile resistance elements into urban and peri-urban aquatic environments, underscoring the need for integrated environmental AMR surveillance.